Induction of apoptosis by a novel copper-based anticancer compound, Casiopeina II, in L1210 murine leukaemia and CH1 human ovarian carcinoma cells - De Vizcaya-Ruiz, A.; Rivero-Muller, A.; Ruiz-Ramirez, L.; Kass, G.E.N.; Kelland, L.R.; Orr, R.M.; Dobrota, M. (Toxicology in vitro, 2000)
The activity of casiopeina II [Cu(1,4-dimethyl-1,10-phenanthroline)(glycine)NO 3], a novel anticancer agent, was tested in two cell lines, L1210 murine leukaemia, CH1 human ovarian carcinoma, cisplatin-resistant and sensitive. Exposure of the cells to a range of concentrations of casiopeina II indicates that this copper complex kills cells by apoptosis and necrosis. Condensed chromatin and nuclear fragmentation were observed after exposure to casiopeina II. The caspase inhibitor Z-Val-Ala-DL-Asp-fluoromethylketone (Z-VAD-FMK) almost completely inhibited apoptosis induced by cisplatin; however, casiopeina II-induced apoptosis was inhibited only by 50–70%. These data are consistent with caspase activation (measured by Z-Asp-Glu-Val-Asp-7-amino-4-trifluoromethylcoumarin; Z-DEVD-AFC) by casiopeina II and cisplatin and confirm that caspases are activated in the apoptotic cell death induced by casiopeina II. DNA fragmentation was observed in L1210 cells, but not in CH1 cells. No difference in susceptibility to induction of apoptosis by casiopeina II was found between sensitive and cisplatin resistant cells. In this work we show that the novel copper-based antineoplastic agent casiopeina II is highly active against murine and human cancer cell lines, including cell lines resistant to cisplatin.